2017
DOI: 10.1377/hlthaff.2017.0556
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Market Concentration Trends In The United States: Evidence And Policy Responses

Abstract: Policy makers and analysts have been voicing concerns about the increasing concentration of health care providers and health insurers in markets nationwide, including the potential adverse effect on the cost and quality of health care. The Council of Economic Advisers recently expressed its concern about the lack of estimates of market concentration in many sectors of the US economy. To address this gap in health care, this study analyzed market concentration trends in the United States from 2010 to 2016 for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
149
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(153 citation statements)
references
References 31 publications
2
149
1
1
Order By: Relevance
“…Injecting greater competition into heavily regulated healthcare markets is a popular reform model in many jurisdictions (Gaynor et al 2016;Glied and Altman 2017;OECD 2012). But this takes place against the backdrop of a long-term trend of provider consolidation in healthcare markets (Gaynor and Town 2012;Fulton 2017). Understanding the relationship between quality and market structure in healthcare is therefore important.…”
Section: Introductionmentioning
confidence: 99%
“…Injecting greater competition into heavily regulated healthcare markets is a popular reform model in many jurisdictions (Gaynor et al 2016;Glied and Altman 2017;OECD 2012). But this takes place against the backdrop of a long-term trend of provider consolidation in healthcare markets (Gaynor and Town 2012;Fulton 2017). Understanding the relationship between quality and market structure in healthcare is therefore important.…”
Section: Introductionmentioning
confidence: 99%
“…The economic pressures on health care systems have influenced practice consolidation and, consequently, increased the geographic scope of patient care. 1 , 2 Major health systems now host patients spread across a large geographic scope, and, as a result, patients are accessing their health care systems from distant locations, particularly for highlyspecialized surgical care. Thus, preoperative anesthetic planning, assessment, and optimization must also be accomplished over greater distances.…”
mentioning
confidence: 99%
“…Second, under Medicare Advantage and Managed Medicaid, the scope of premiums has been greatly expanded; however, insurers do not necessarily offer coverage in the traditional group market [15,16]. Nevertheless, our paper is the first to use this novel Wall Street database to provide a different perspective from that of publicly traded healthcare insurance companies to reach similar conclusions to current studies, namely that at an aggregate level, the U.S. health insurance market has become less concentrated over the past decade [8].…”
Section: Discussionmentioning
confidence: 64%
“…These issues are, however, challenging to examine on a national scale, in part due to the difficulty in obtaining comprehensive data for the multitude of insurers that exist [5,6]. Citing calls by policymakers for additional evidence, a recent study found that 57% of U.S. metropolitan statistical areas were highly concentrated for insurers in 2016, with mean measures of market concentration declining by 1% between 2011 and 2016 [8].…”
Section: Introductionmentioning
confidence: 99%